2006
DOI: 10.1099/jmm.0.46632-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine secretion profiles of human keratinocytes during Trichophyton tonsurans and Arthroderma benhamiae infections

Abstract: Dermatophytes cause intractable superficial infections in humans. Arthroderma benhamiae, a zoophilic dermatophyte, triggers severe inflammatory responses in humans, while Trichophyton tonsurans, an anthropophilic dermatophyte, triggers minimal ones. Cytokines and other factors derived from keratinocytes play important roles in inflammatory and immune responses in the skin. The authors performed an in vitro investigation to determine the human keratinocyte cytokine profiles during dermatophyte infection. The hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 42 publications
1
82
1
6
Order By: Relevance
“…The group of cytokines secreted includes IL-4, IL-6, IL-8, IL-10, IL-13, and MIP-1β. The expression of 6,8,10, and 13 has been observed in keratinocytes under pathological conditions as an inflammatory response (Shiraki et al, 2006). The increased expression of IL-6 and IL-8 has been shown in a murine wound healing model (Bryan et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…The group of cytokines secreted includes IL-4, IL-6, IL-8, IL-10, IL-13, and MIP-1β. The expression of 6,8,10, and 13 has been observed in keratinocytes under pathological conditions as an inflammatory response (Shiraki et al, 2006). The increased expression of IL-6 and IL-8 has been shown in a murine wound healing model (Bryan et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…It was shown that Arthroderma benhamiae, a zoophilic dermatophyte and teleomorph of T. mentagrophytes, induces the expression of various cytokines by keratinocytes, which may be involved in the development of an inflammatory response, typical of these infections. 33 Nevertheless, the authors affirm that these cells, when in contact with T. tonsurans, an anthropophilic dermatophyte, showed a limited cytokine expression, which probably explains the low inflammatory response provoked in lesions caused by this species. Other authors also described a difference in the profile of cytokine expression by keratinocytes infected in vitro by T. mentagrophytes, T. rubrum and T. tonsurans, which would also explain the difference in the intensity of induced inflammatory responses during infection by these species.…”
Section: Host-dermatophyte Interaction and The Pathogenesis Of Dermatmentioning
confidence: 97%
“…Activation of CD1d-restricted invariant NKT (iNKT) cells enhances host resistance to some microbes in a manner dependent on the level of CD1d expression on APCs (29,30). In contrast, the activation of iNKT cells promotes susceptibility to some microbes (3,28). For instance, in the murine lung, the immune responses of iNKT cells to two very closely related microbes, Chlamydia pneumoniae and Chlamydia muridarum, are protective and harmful, respectively (19).…”
mentioning
confidence: 99%
“…Intracellular signaling mediated by surface CD1d utilizes NF-B, a well-known immune-related transcription factor (32,38). CD1d-restricted NKT cells can act directly on infected cells, killing CD1d-expressing cells (28). They can also modulate adaptive immune cells by altering Th1-Th2 polarization.…”
mentioning
confidence: 99%